Is the Religious Left Resurgent? - Baker, Joseph O. (Sociology of religion, 2020)
Journalistic sources seem to suggest that there has been a resurgence of the American Religious Left (i.e., politically liberal Christians who support progressive agendas) in the wake of the strong support from the conservative Christian right in the 2016 presidential election of Donald J. Trump. Using quantitative analysis, we draw on survey data from the General Social Survey, the Public Religion Research Institute, and the National Congregations Study to assess the possibility of a resurgence among the Religious Left. In comparison with a speculated rise, our analysis indicates a notable decline in both the prevalence and engagement of Americans who self-identify as both religious and politically liberal. Not only is the constituency of the Religious Left shrinking, they have also been steadily disengaging from political activity in the last decade. Especially when looking at more recent elections, it has been those among the Secular Left who have been the most politically engaged. We summarize these empirical patterns in relation to the Religious Right and consider the potential for influence among the Religious Left aside from electoral politics. We also briefly consider other possibilities for their political impact and reflect on the inadequacy of the label "Religious Left" for capturing important dynamics. In the end, we urge greater attention to politics among sociologists of religion, providing a set of research questions to consider in light of the upcoming American 2020 national election.